The Effect of Muri-Q Method on the Ability of Tahfizh al-Qur’an in Early Childhood - Elfara Hajjar Sujani; Ichsan Ichsan (Tamaddun, 2022)
There are various methods that educators can use to improve the ability of tahfizh al-Qur'an of the children in their early childhood. One of them is Muri-Q method. This study aims to determine whether Muri-Q method's effect on the ability of tahfizh al-Qur'an and how significant its effect on the ability of tahfizh al-Qur'an of the children in their early childhood at TKQ Kharisma Haramain Sukoharjo, Central Java. The research method used was descriptive quantitative with a correlational design. The data colletion techniques used were by conducting pre-test and post-test, observation, and interviews. The population in this study was all students at TKQ Kharisma Haramain. The research subjects were 20 students of class B at TKQ Kharisma Haramain. The research data were analyzed using IBM SPSS version 28 application. The analysis method used was t-test with a significance level of <0.001. The result of the data analysis was that there was a significant difference between the pre-test and post-test. Therefore, it can be concluded that Muri-Q method affected children’s tahfizh al-Qur’an ability at TKQ Kharisma Haramain.